2019
DOI: 10.1002/pchj.282
|View full text |Cite
|
Sign up to set email alerts
|

A well‐slept teacher is a better teacher: A multi‐respondent experience‐sampling study on sleep, stress, and emotional transmission in the classroom

Abstract: The present study examined the impact of sleep, stress, and negative activating emotions of high-school teachers on their students' affective experience, academic motivation, and in-class satisfaction. It is hypothesized that teachers' sleep quality and stress have a positive influence on their own nervousness and irritability. With reference to the emotional crossover theory, teachers' nervousness and irritability are hypothesized to intensify students' nervousness and irritability and subsequently dampen the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
23
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(23 citation statements)
references
References 66 publications
(82 reference statements)
0
23
0
Order By: Relevance
“…In fact, a positive relationship has been shown between teachers' subject-specific enthusiasm and student performance [12]. Furthermore, enthusiasm has been demonstrated as an important teacher quality [13], and a well-slept teacher has been shown preferable for students' academic motivation and in-class satisfaction [14]. Conversely, teachers being perceived as bored may reduce students' learning motivation [15].…”
Section: Discussionmentioning
confidence: 99%
“…In fact, a positive relationship has been shown between teachers' subject-specific enthusiasm and student performance [12]. Furthermore, enthusiasm has been demonstrated as an important teacher quality [13], and a well-slept teacher has been shown preferable for students' academic motivation and in-class satisfaction [14]. Conversely, teachers being perceived as bored may reduce students' learning motivation [15].…”
Section: Discussionmentioning
confidence: 99%
“…However, beyond a general concern for the well-being and welfare of America's teachers, there is reason to believe that teacher stress has implications beyond the individuals directly affected by that stress. Instead, if teacher stress is related to long-term health problems or poor work performance, it stands to reason that the cumulative effects may not only impact daily teacher performance, but could also have important implications for students (Poon, Hui, Yuen, Kwong, & Chan, 2019). In fact, research has shown that teacher stress is contagious, and that teacher mental health can also influence student well-being (Becker, Goetz, Morger, & Ranellucci, 2014;Milkie & Warner, 2011;Oberle & Schonert-Reichl, 2016;Schonert-Reichl, 2017).…”
Section: Final Thoughtsmentioning
confidence: 99%
“…But the study of emotions, their application in the classroom, and the need for the existence of a good classroom climate for a beneficial, motivating and interesting educational process has not been sufficiently studied (Garritz, 2009), despite the need for teachers to carry out good emotional management and to possess strategies for resolving conflicts (Bonilla et al, 2020). What we know today is that teachers with high levels of stress reported also higher levels of anxiety and depression and that may also influence the student's affective experience in learning (Poon et al, 2019) but also a positive association between teachers and students positive emotions have been found in science lessons (Frenzel et al, 2009).…”
Section: Emotions In Teaching and Learningmentioning
confidence: 99%